2003
DOI: 10.1242/jeb.00588
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seasonal temperature on the repeat swimming performance of rainbow troutOncorhynchus mykiss

Abstract: ). Given that metabolic recovery in skeletal muscle (muscle lactate, ATP and glycogen, but not PCr) occurs more rapidly at warm than cold temperatures in exhausted rainbow trout Oncorhynchus mykiss and Atlantic salmon Salmo salar (Kieffer et al., 1994;Wilkie et al., 1997;Kieffer, 2000), the expectation is that swimming performance is restored faster at a higher temperature. This expectation would be consistent with the known increase in both maximum oxygen uptake and maximum cardiac output with temperature (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
116
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(132 citation statements)
references
References 59 publications
10
116
6
Order By: Relevance
“…Overall, however, the Modified Bell and Terhune model developed in the present study from iterated estimates for λ and A exp provided the best fit to the data. Values of the λ-shape coefficient reported in the literature range from 0.50-0.53 [4,8,10,24]. The λ-shape coefficient in this study was 0.5, confirming its use for the fusiform body shape of the grouper species used in this study.…”
Section: Discussionsupporting
confidence: 75%
“…Overall, however, the Modified Bell and Terhune model developed in the present study from iterated estimates for λ and A exp provided the best fit to the data. Values of the λ-shape coefficient reported in the literature range from 0.50-0.53 [4,8,10,24]. The λ-shape coefficient in this study was 0.5, confirming its use for the fusiform body shape of the grouper species used in this study.…”
Section: Discussionsupporting
confidence: 75%
“…This was further supported by a higher net COT, indicating that swimming at 23°C was relatively more costly. Similarly, in warm-acclimated rainbow trout, the repeated swimming performance was found to be reduced because exercise recovery was slower compared with colder acclimated fish (Jain and Farrell, 2003). Therefore, this may partially explain a lower U crit at 23°C.…”
Section: Physiological Limitations At High Temperaturesmentioning
confidence: 97%
“…Jain & Farrell (2003) proposed that fish may opt to swim to different U crit levels depending on either the water temperature or a resulting physiological condition. They found that warm-acclimated (14.9°C) rainbow trout were able to achieve greater U crit1 values than cold-acclimated (8.4°C) fish through increased use of anaerobic swimming.…”
Section: Discussionmentioning
confidence: 99%